2019
DOI: 10.3390/wevj10030050
|View full text |Cite
|
Sign up to set email alerts
|

Under Pressure—Users’ Perception of Range Stress in the Context of Charging and Traditional Refueling

Abstract: Although electric drives can locally reduce the environmental impact of traffic, the penetration rates of battery electric vehicles (BEV) are far below expectations, not least because the charging infrastructure network is still considered insufficient by potential users. Therefore, the planning of charging infrastructure that considers both needs and user requirements is essential to remove an important barrier to widespread adaptation of e-vehicles, but it is also a challenge. A better understanding of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Despite the high growth rate of charging stations over the past decade, many internal combustion-engine vehicle users still believe that EV charging stations are not widely available in many regions, especially in developing countries. The limited number of charging stations together with the limited capacity of batteries in EVs has caused the issue of "range stress" or "range anxiety" [8] and impeded the mass adoption of EVs [28,29].…”
Section: Barrier To Expanding Charging Stations: High Investment Costs and Low Profitabilitymentioning
confidence: 99%
“…Despite the high growth rate of charging stations over the past decade, many internal combustion-engine vehicle users still believe that EV charging stations are not widely available in many regions, especially in developing countries. The limited number of charging stations together with the limited capacity of batteries in EVs has caused the issue of "range stress" or "range anxiety" [8] and impeded the mass adoption of EVs [28,29].…”
Section: Barrier To Expanding Charging Stations: High Investment Costs and Low Profitabilitymentioning
confidence: 99%
“…Bearing in mind the need to promote eco-friendly solutions, electromobility, including electric vehicles, is one of the trends which calls for further promotion [29]. One of the reasons why the development of electromobility is hampered appears to be the travelling population's anxiety about the limitations caused by the necessity of the vehicle recharging on-route, referred to as range anxiety (more broadly discussed in [30,31], inter alia). At the same time, it should be noted that vehicle recharging by means of municipal charging stations usually proceeds much faster than charging at home.…”
Section: Discussionmentioning
confidence: 99%
“…However, such trials may be limited in their duration and by the driving range capabilities of the EV trialled at the time. In contrast, Philipsen et al (2019) compared EV range concerns in participants who had different extents of ICEV driving and EV driving experience. They found that those with two or more years of experience driving an EV were significantly less concerned about low battery levels and inadequate driving range than those with no EV experience.…”
Section: Experience and Trustmentioning
confidence: 99%